Nyadranan, Bentuk Akulturasi Islam dengan Budaya Jawa - Muh. Barid Nizarudin Wajdi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: Nyadran is the symbol of a connection with ancestors , nature and fellow. its a ritual pattern that mixes the local culture and values of Islam , so that the very existence of the locality that still seemed tinged with Islamic values . Thus it is not surprising if the execution of the Nyadran still has to do with the culture of Buddhist and Hindhu-animism which is then assimilated with Islamic values by Wali Songo . Furthermore, this study will investigate how the linkage between Nyadranan and Islamic values. Qualitative research approach was applied to answer the research question. This study was conducted in Baron, Nganjuk City. Observation and depth interview were applied to collect data. This result indicated that it is a meaningful relation . Nyadran is an expression of social of the community, solidarity and togetherness being the main pattern of this tradition . This expression will ultimately produce a vertical-horizontal relationship more intimate . In this context , then the Nyadran will be able to improve the pattern of relationship between God and society (social ) , and thus eventually will promote the development of culture and tradition that has developed into a more sustainably.Keywords: Gender equity, Elementary School, gender fair education, learning environment.